2023
DOI: 10.1186/s12967-023-03978-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic classifications of renal cell carcinoma reveal intrinsic connections with clinical and immune characteristics

Abstract: Background Kidney cancer undergoes a dramatic metabolic shift and has demonstrated responsiveness to immunotherapeutic intervention. However, metabolic classification and the associations between metabolic alterations and immune infiltration in Renal cell carcinoma still remain elucidative. Methods Unsupervised consensus clustering was conducted on the TCGA cohorts for metabolic classification. GESA, mRNAsi, prognosis, clinical features, mutation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Current studies have reported that ACAA2 is a prognostic factor in IDH mutation lower‐grade glioma 29 . The downregulation of ACAA2 promotes the progression of renal cell carcinoma and liver cancer 30,31 . It is reported that ACAA2, as a BNIP3 binding partner, provides a possible link between fatty acid metabolism and apoptosis in human hepatoma HepG2 cells and U2OS osteosarcoma cells 32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current studies have reported that ACAA2 is a prognostic factor in IDH mutation lower‐grade glioma 29 . The downregulation of ACAA2 promotes the progression of renal cell carcinoma and liver cancer 30,31 . It is reported that ACAA2, as a BNIP3 binding partner, provides a possible link between fatty acid metabolism and apoptosis in human hepatoma HepG2 cells and U2OS osteosarcoma cells 32 .…”
Section: Discussionmentioning
confidence: 99%
“…ACAA2 is a ligand‐dependent coactivator of thyroid hormone receptor β1 9 . In kidney cancer, ACAA2 is a tumor suppressor, associated with higher immune invasion and elevated PD‐1 expression in CD8+ T cells 10 . ACAA2 is a key factor linking tumor metabolism and tumor immunity 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACAT1 inhibition promoted the proliferation of CD8 + T cells and increased plasma membrane cholesterol levels. Together, anti-PD-1 antibodies and ACAT1 inhibitors have shown increased anti-tumor effectiveness [ 96 ]. Anti-PD-1 immunotherapy is not highly effective at treating nasopharyngeal cancer, despite the reality that CD8 + T cells are prevalent in the immune environment.…”
Section: Lipid Metabolism and Cancer Therapymentioning
confidence: 99%